FamilyPso – a new questionnaire to assess the impact of psoriasis on partners and family of patients. (22nd August 2016) - Mrowietz, U.; Hartmann, A.; Weißmann, W.; Zschocke, I.
Abstract: Background: Psoriasis is a lifelong disease for which there is no cure. It has been conclusively shown across all ethnicities that patients suffering from psoriasis have a significantly reduced health‐related quality of life and a high disease burden. Objective: Surprisingly little is known about the impact of a patient's psoriasis on partners or family members. Methods: To address this issue a systematic literature search has been conducted and interviews with relatives of psoriasis patients living in the same household were performed. From this collected information, items were generated that were commonly mentioned to affect living and tested in a large group of relatives before the final item selection was done. Results: A first set of 29 items was selected and tested in a study with 96 patient relatives. After adjustment and statistical analysis, the final FamilyPso questionnaire was condensed to 15 items to assess the burden of partners or family members living together with psoriasis patients. Conclusion: The FamilyPso enables physicians to achieve a better understanding of the impact of psoriasis as a lifelong chronic disease on partners and the family environment.